2016
DOI: 10.1158/0008-5472.can-15-2921
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stress-Induced Phosphorylation of KAP1 Ser473 Blocks Mitochondrial Fusion in Breast Cancer Cells

Abstract: Mitochondrial dynamics during nutrient starvation of cancer cells likely exert profound effects on their capability for metastatic progression. Here we report that KAP1 (TRIM28), a transcriptional co-adaptor protein implicated in metastatic progression in breast cancer, is a pivotal regulator of mitochondrial fusion in glucose-starved cancer cells. Diverse metabolic stresses induced Ser473-phosphorylation of KAP1 (pS473-KAP1) in a ROS- and p38-dependent manner. Results from live cell imaging and molecular stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 49 publications
5
68
0
Order By: Relevance
“…4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells. 25,62 To better understand the regulatory role of DRP1 in cancer metabolism, we used [U- 13 C] glucose tracing to directly reveal the intracellular glucose metabolism in DRP1-deficient H460 lung cancer cells and in multiple mdivi-1-treated cancer cell lines.…”
Section: Discussionsupporting
confidence: 74%
“…4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells. 25,62 To better understand the regulatory role of DRP1 in cancer metabolism, we used [U- 13 C] glucose tracing to directly reveal the intracellular glucose metabolism in DRP1-deficient H460 lung cancer cells and in multiple mdivi-1-treated cancer cell lines.…”
Section: Discussionsupporting
confidence: 74%
“…4c ), a molecule previously speculated to function as an RNA-binding protein 40 . More recent evidence suggests that TRIM28 plays an oncogenic role in numerous human malignancies 41 44 , including several studies linking TRIM28 to the metastatic progression of breast cancers 17 , 45 47 . Interestingly, the ability of TRIM28 to enhance the malignancy of breast cancer cells transpires in part through its transcriptional repression of both p21 and gadd45a 15 , 16 , 18 , two transcripts whose expression is negatively regulated by BORG in D2.OR cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KAP1 can be subjected to several post-translational modifications (PTM) including sumoylation, ubiquitination and phosphorylation. Among these, phosphorylation on serine 473 (S473) was observed in the setting of DNA damage ( 35 ), metabolic stress ( 36 ), T cell receptor activation ( 37 , 38 ) and KSHV (Kaposi's sarcoma-associated herpervirus ) infection ( 39 ), and to be mediated by PKCδ (Protein Kinase C δ) during S phase ( 40 ). We thus examined the influence of the cell cycle on this KAP1 PTM by performing IF with a pS473KAP1-specific antibody on NIH3T3 cells synchronized by 3 days of serum starvation followed by serum re-addition.…”
Section: Resultsmentioning
confidence: 99%